Development of Closed Distribution Monitoring System, Case Study: 3-kg LPQ Distribution in Malang, Indonesia - Wasis Wicaksono, Galih; Kesy Garside, Annisa; ., Zulfatman (International Journal of Engineering and Technology, 2026)
Since a few years ago, supply, distribution, and price regulation of 3-kg Liquefied Petroleum Gas (LPG) has been fully handled by the Indonesian government. Distribution of the LPG has been monitored by a system named 3-kg LPG Distribution Monitoring System (SI-MOL3K). It was developed in a closed distribution model from suppliers to consumers through registered agents and distributors. How-ever, the SIMOL3K has been prepared only to control the distribution by the control card up to distributors. It does not have the capabil-ity to arrange area of distribution for agents and distributors. Hence, in practice there exist overlapping area of distribution and extension of distribution chain. Consequently, the price in distributors and sub-distributors cannot be controlled properly. Considering those prob-lems, this study is aimed to develop a new closed distribution monitoring system to set the controlled distribution by the control card up to distributors with clear area of distribution. The new system is built by involving SPPBE’s, agents, distributors, and consumers in Ma-lang-Indonesia based on mapping location and area of distribution. Results of the study shows that the system can successfully cover the distribution from LPG Filling and Bulk Carrier Station (SPPBE) to distributors by including mapping of location and area of distribution.